Developing Audio Visual Media in Teaching Recount Texts for the Tenth Grade Students of Madrasah Aliyah - Reka Hayati Rahmah; Atni Prawati; Dahnilsyah Dahnilsyah (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to develop audio-visual media in learning recount text for grade 10 MAN and to find out the level of validity of the media that has been developed. The lack of available media and students' disinterest in the learning process, which makes them less engaged in class, are the driving forces behind the development of learning media audio-visual. This research uses development research using 4D models. This research was conducted in three stages, namely 1) definition which consists of front-end analysis, student analysis, material analysis, and concept analysis. 2) design which consists of making draft storyboards and editing media. 3) development, namely the stage to get validation from experts. The results of this study indicate that the learning media was developed in the recount text material got an average score of 86.5% with very valid criteria. This means that this product is worthy of being tested to become a learning video in recount texts material.